I'm Too Old for This: Time Demands and Older, Early-Career Employees' Receptivity to Supervisor Support. (April 2020) - Dust, Scott B.; Wang, Peng; Lai, Lei
This study explores how age and career stage affect receptivity to supervisor support using a multi-wave field sample of 528 employees. Following conservation of resources theory, we suggest that for early-career employees, supervisor support will more strongly mitigate the negative relationship between time demands and satisfaction with work–family balance and career satisfaction. We argue, however, that prior research overlooks a demographic with unique resource valuations: older, early-career employees. We therefore hypothesize and test two-way and three-way interactions of time demands, supervisor support, and career stage on satisfaction with work–family balance and career satisfaction. Our findings illustrate that early-stage employees were more receptive to the buffering impact of supervisor support. Additionally, for early-career employees, older employees compared to younger employees were more receptive to the buffering impact of supervisor support with regard to satisfaction with work–family balance and less receptive with regard to career satisfaction.